2015
DOI: 10.1016/j.ijresmar.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Strategic performance effects of misaligned formal contracting: The mediating role of relational contracting

Abstract: Authors are permitted to self-archive the peer-reviewed (but not final) version of a contribution on the contributor's personal website, in the contributor's institutional repository or archive, subject to an embargo period of 24 months for social science and humanities (SSH) journals and 12 months for scientific, technical, and medical (STM) journals following publication of the final contribution. Although all errors remain our own, we gratefully acknowledge Robert Dahlstrom, Matilda Dorotic, Mrinal Ghosh, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Specifically, our findings shed light on the relationship between contractual and relational governance by detailing the influence of contract specificity on relational behaviors over time (aspects not taken into account by Lusch and Brown 1996 or Poppo and Zenger 2002). Furthermore, by departing from prior research that has predominantly studied how relational behaviors influence performance (e.g., Bercovitz, Jap, and Nickerson 2006; Hoppner and Griffith 2011; Lusch and Brown 1996; Sande and Haugland 2015), this work extends the literature by examining the moderating role of new product success on the relationship between contract specificity and relational behaviors. As such, we provide a more robust perspective of ongoing manufacturer–retailer relationships.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, our findings shed light on the relationship between contractual and relational governance by detailing the influence of contract specificity on relational behaviors over time (aspects not taken into account by Lusch and Brown 1996 or Poppo and Zenger 2002). Furthermore, by departing from prior research that has predominantly studied how relational behaviors influence performance (e.g., Bercovitz, Jap, and Nickerson 2006; Hoppner and Griffith 2011; Lusch and Brown 1996; Sande and Haugland 2015), this work extends the literature by examining the moderating role of new product success on the relationship between contract specificity and relational behaviors. As such, we provide a more robust perspective of ongoing manufacturer–retailer relationships.…”
Section: Discussionmentioning
confidence: 94%
“…This finding extends the extant literature (e.g., Buvik and John 2000; Gulati and Singh 1998; Lusch and Brown 1996; Mooi and Ghosh 2010; Poppo and Zenger 2002) by providing a better understanding of how retailers behave under contractual terms. Specifically, our findings indicate that retailers will scale back investments that are not easily measurable (e.g., relational behaviors) when contracts are less specific, laying a foundation for further research that could examine contract (mis)alignment (cf., Ghosh and John 1999; Sande and Haugland 2015) and its influence on relational governance over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contract completeness and symmetric dependence, as economic mechanisms, demonstrate mutually specified contractual clauses and relationship specific investments (Brown et al, 2000;Liu et al, 2017b). Contractual governance is albeit ubiquitous and offers an institutional framework, regulating course of relationship exchange (Luo, 2009;Liu et al, 2017b), it varies in the level of completeness, complexities (Crocker & Reynolds, 1993), rigidity, and flexibility (Sande & Haugland, 2015). Several researchers have maintained that contracts will always be incomplete due to inevitable unpredictability (Crocker & Reynolds, 1993;Luo, 2009).…”
Section: Economic Governance Mechanismsmentioning
confidence: 99%
“…Research in marketing has indicated the potential endogeneity of governance, given that the alignment between governance mechanisms and transactional characteristics can result in better performance (e.g., Mooi and Gilliland 2013; Sande and Haugland 2015). Acknowledging this possibility, we explicitly test for the exogeneity of the contractual completeness and monitoring and enforcement constructs separately for each equation, with perfunctory and consummate compliance as dependent variables, using instrumental variables (IVs) (Sargan 1958), a procedure commonly used to address endogeneity concerns.…”
Section: Model Specificationmentioning
confidence: 99%